UTILIZATION OF A SOCIAL MEDIA PLATFORM TO DEVELOP CONTINUING EDUCATION PROGRAMMING FOR PROMOTING NURSING PRACTICE IN CAMBODIA - Karen Simon Reed (Belitung Nursing Journal, 2019)
Background: Cambodia’s nursing profession and nursing education system continue to progress 40 years after destruction by the Khmer Rouge. The author, who has a relationship with a hospital in southern Cambodia, was asked to teach physical assessment techniques to improve patient care. Objective: This study aimed to evaluate the impact of culturally congruent physical assessment media on the knowledge-base of Cambodian nurses. Methods: This article describes two years of an on-going project designed by the author who annually recruits US based BSN nursing students to use the ADDIE model to create and record segments on physical assessment which are posted on a private You Tube channel for the limited English- speaking Cambodian nursing staff. Optional post-tests are administered by the Cambodian hospital’s nursing director. Results: Test results reflect knowledge gained on cardiac, pulmonary, and gastrointestinal physical assessment skills with means ranging from 73.55% to 95.71%. Physical assessment skills until recently were not taught in Cambodia's nursing programs. Cambodia's nursing profession is advancing and a corresponding skill set including conducting physical assessments is necessary. As a majority of the project participants did not have prior exposure to the material, a pre-test was not provided and participation in post-testing was optional. The objective was to provide useful professional educational materials at a comfortable language level for the Cambodian nurses using examples which were culturally relevant. Conclusion: The BSN students successfully developed culturally relevant educational products the Cambodian nurses found useful.